Aplikasi Pengurusan Kecergasan Atlet Kayak UTHM: Application of UTHM Kayak Athletes Fitness Management - Yazid, Muhammad Faris; Mohd Yasin, Suhaila (Applied Information Technology And Computer Science, 2021)
UTHM Kayak Athlete Fitness Management Application is an application developed for the use of kayak athletes and coaches in preparation for competitions. The system is based on the Android operating system. The manual system used today is less practical and poses various problems in terms of attendance, activity schedule and healthy eating. The physical use of paper is capable of making it easily lost from custody. Coaches often use paper to record attendance and generate a schedule which in turn will cause the paper to be torn or lost and cause the coach to lose data. The purpose of this application developed is to overcome such problems and in turn facilitate the management of coaches to monitor athletes. This application is a medium for athletes and coaches to update all information related to the sport of kayaking as a reference. The methodology used to develop this application is a staged prototype model. This approach is very effective in the process of developing a software because it can reduce complexity. It only requires focusing on one part at a time and saves time in identifying functions that are not working properly. The system was developed using Android Studio as the programming medium and Firebase as the database medium. The system should be able to run well especially on key modules such as login using a valid password and username, QR code can be generated perfectly, activity schedule can be updated constantly, nutrition information can be updated, reports can be generated as coach reference and the system is able to notify users after any updates are made.